Activity of Bacteriophages in Removing Biofilms of Pseudomonas aeruginosa Isolates from Chronic Rhinosinusitis Patients - Fong, Stephanie A.; Drilling, Amanda; Morales, Sandra; Cornet, Marjolein E.; Woodworth, Bradford A.; Fokkens, Wytske J.; Psaltis, Alkis J.; Vreugde, Sarah; Wormald, Peter-John (Frontiers in Cellular and Infection Microbiology, 2017)
Introduction: Pseudomonas aeruginosa infections are prevalent amongst chronic rhinosinusitis (CRS) sufferers. Many P. aeruginosa strains form biofilms, leading to treatment failure. Lytic bacteriophages (phages) are viruses that infect, replicate within, and lyse bacteria, causing bacterial death. Aim: To assess the activity of a phage cocktail in eradicating biofilms of ex vivo P. aeruginosa isolates from CRS patients. Methods: P. aeruginosa isolates from CRS patients with and without cystic fibrosis (CF) across three continents were multi-locus sequence typed and tested for antibiotic resistance. Biofilms grown in vitro were treated with a cocktail of four phages (CT-PA). Biofilm biomass was measured after 24 and 48 hours, using a crystal violet assay. Phage titrations were performed to confirm replication of the phages. A linear mixed effects model was applied to assess the effects of treatment, time, CF status, and multidrug resistance on the biomass of the biofilm. Results: The isolates included 44 strain types. CT-PA treatment significantly reduced biofilm biomass at both 24 and 48 hours post-treatment (p<0.0001), regardless of CF status or antibiotic resistance. Biomass was decreased by a median of 76% at 48 hours. Decrease in biofilm was accompanied by a rise in phage titres for all except one strain. Conclusion: A single dose of phages is able to significantly reduce biofilms formed in vitro by a range of P. aeruginosa isolates from CRS patients. This represents an exciting potential and novel targeted treatment for P. aeruginosa biofilm infections and multidrug resistant bacteria.